Growth Changes In Facıal Dımensıons And Growth Of Other Parts Of The Body Durıng Adolescence - İzzet Duyar (Galenos Yayinevi, 1998)
The main purpose of this study is to evaluate growth relations between facial dimensions (nasion-gnathion and zygion-zygion) and some other parts of the body including head and postcranial dimensions. Furthermore, gender differences during the adolescence period are examined. The sample was taken from an anthropometric study, which aimed at constructing optimal growth standards for 12 to 17-year-old Turkish adolescents. Each sex and age group consisted of 100 subjects from seven selected cities, representing the seven geographical regions of Turkey. In order to evaluate the relationships between face and other parts of the body, 15 measurements were taken following the direce-tieons provided by IBP (International Biological Programme). Regression analysis was used to assess the relationships between face and other body dimensions. Regression analysis indicated that growth of the facial height had a stronger relationship with postcranial dimensions than those of head dimensions, except nose height. The results showed that the vertical growth of face was more similar to "breadth" measurements of head than postcranial dimensions. As to sexual differences, incremental growth relationships in boys were stronger than girls in all variables studied.